Electric field-induced structural transition of domain walls in nanoconfined nematic liquid crystal systems. Issue 1 (2nd January 2019) - Chen, Sibo; Zhou, Xuan; Zhang, Jing; Zhang, Zhidong
ABSTRACT: The electric field-induced structural transition of domain walls in nanoconfined nematic liquid crystal systems was investigated on the basis of Landau–de Gennes theory. Two models of nanoconfined domain wall systems were established as splay–bend and twist wall systems under Fréedericksz transitions with two different rotation directions under the effect of electric field E / E 0 . Results showed that two structural transition processes occur in both models. Pincement transition occurs under a critical external field E c1 / E 0 . In pincement transition, walls change into two squeezed symmetric surface defects with opposite charges. Surface defects spread along the direction of the substrates and attain surface order reconstruction states as E / E 0 is enhanced to E c2 / E 0 . The increment in cell gap d from the nanoscale to the microscale will not affect E c2 / E 0 in both models. GRAPHICAL ABSTRACT: